Teori Pembangunan dalam Perspektif Ibnu Khaldun : Analisis Historis dan Implikasi Kontemporer - Ade Suryawirawan; Yadi Janwari; Dedah Jubaedah (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Ibn Khaldun's thoughts, especially those presented in his work Muqaddimah, have made important contributions to understanding the dynamics of society, economy, and politics. This article comprehensively examines Ibn Khaldun's development theory with a historical approach, conceptual analysis, and reflection on the relevance of his thoughts in the modern era. Using literature study and content analysis methods, this study explores central concepts such as asabiyyah, dynasty cycle, economic productivity, and the role of the state in development. The findings show that although issued in the 14th century, Ibn Khaldun's development theory has essential similarities with contemporary development paradigms such as the importance of social capital, fiscal balance, and leadership regeneration. The theoretical implications of this study are expected to enrich the discourse on development based on ethical values ​​and social justice.